Factory Automation, Labor Demand, and Local Labor Market - Daiji Kawaguchi; Tetsuji Okazaki; Xuanli Zhu (Institute of Labor Economics (IZA), 2024)
This study examines the impact of a technological change on employment and wages, focusing on the adoption of power looms in the silk-weaving industry. Exploiting plant-level panel data from 20th century Japan, we demonstrate that at the plant level, the power loom adaption increased the employment and wages of adult male workers, who likely conducted engineering tasks, and moderately increased wages of female adults, who were simultaneously displaced and reinstated to more non-routine tasks. The wage hike of adult workers induced the exit of less efficient plants and decreased female adult employment by 28 percent at the area level.
Keywords: J23; J24; J31; N35; 330; electrification; automation; employment; wage; second industrial revolution